2010
DOI: 10.1007/s11095-010-0133-7
|View full text |Cite
|
Sign up to set email alerts
|

Microneedles with Intrinsic Immunoadjuvant Properties: Microfabrication, Protein Stability, and Modulated Release

Abstract: Microneedles containing PCPP coatings provide improved protein stability, modulated release, and protein-friendly microfabrication process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…Consequently, thermal and mechanical properties of PPZ greatly vary with T g ranging from −10 to 35 °C, contact angle 63°-107°, tensile strength 2.4-7.6 MPa, and modulus of elasticity 31.4-455.9 MPa [264]. PPZ are fabricated into particles, micelles, microneedle coatings, and gels for the delivery of anti-inflammatory drugs, chemotherapeutics, growth factors, DNA, proteins, and vaccines [265][266][267][268]. Moreover, PPZ scaffolds composed of films, fibers, and microspheres are used to assist nerve regeneration and orthopedic applications, alone or blended with polyesters to increase mechanical strength and provide a moderate pH microenvironment for developing tissues [269][270][271].…”
Section: Polyphosphazenesmentioning
confidence: 99%
“…Consequently, thermal and mechanical properties of PPZ greatly vary with T g ranging from −10 to 35 °C, contact angle 63°-107°, tensile strength 2.4-7.6 MPa, and modulus of elasticity 31.4-455.9 MPa [264]. PPZ are fabricated into particles, micelles, microneedle coatings, and gels for the delivery of anti-inflammatory drugs, chemotherapeutics, growth factors, DNA, proteins, and vaccines [265][266][267][268]. Moreover, PPZ scaffolds composed of films, fibers, and microspheres are used to assist nerve regeneration and orthopedic applications, alone or blended with polyesters to increase mechanical strength and provide a moderate pH microenvironment for developing tissues [269][270][271].…”
Section: Polyphosphazenesmentioning
confidence: 99%
“…Andrianov et al reported that the thermal stability of protein and its ability to withstand extreme manufacturing conditions were higher when the protein was in a solution of PCPP coated on solid microneedles as compared to aqueous solution. [36] Modulated protein release was observed from microneedles because of the ion-complexing property of PCPP along with salts of multivalent ions, such as calcium chloride and spermine.…”
Section: Materials Used To Constitute Microneedlesmentioning
confidence: 99%
“…[18] An aqueous polymeric blend was filled in the moulds to fabricate microneedles. Polymeric microneedles can also be fabricated using casting, [36] injection moulding and hot embossing. [18] Chen et al presented a robust Gas-jet coating method to achieve uniform coating of a range of immunotherapeutics, like antigens, DNA and proteins, on microneedles.…”
Section: Fabrication Of Microneedlesmentioning
confidence: 99%
“…Further in vivo studies with these formulations will research the ability of these systems controlled-release pDNA expression. But the results showed that the total number of positive expression was less than solution prescription in 24 h. However, due to the design, the drug can only be loaded onto the surface of MNs, so the drug loading amount is relatively low [23][24][25]. The cost of fabrication is also another concern.…”
Section: Problems Of Non-hydrogel Mnsmentioning
confidence: 99%